Implementasi Algoritma XGBoost dengan Walk Forward Validation untuk Prediksi Harga Emas Antam - Hisyam, Mochammad; Fitri, Zahratul; Aidilof, Hafizh Al Kautsar (Universitas Budi Darma, 2025)
Accurate gold price prediction is crucial in supporting financial and investment decision-making. This study aims to develop and optimize a daily gold price prediction model using the Extreme Gradient Boosting (XGBoost) algorithm based on historical price data and technical indicators. The model was constructed to predict two types of prices, namely